Decreases in encounter rate of endangered Northeast Pacific humpback whales in Southern Costa Rica: Possible changes in migration pattern due to warming events - Pelayo-González, Lili; Herra-Miranda, David; Pacheco-Polanco, Juan Diego; Guzmán, Héctor M.; Goodman, Sierra; Oviedo, Lenin (Frontiers in Marine Science, 2022)
Warming events in the Pacific Ocean are becoming more frequent, intense, and on a larger temporal and spatial scale. This has caused critical habitats of marine species to lose their quality and marine organisms respond by modifying their critical feeding and reproduction behaviors, as well as their distribution. The Northeast Pacific humpback whale of the Central America distinct population segment (DPS) remains Endangered due to its small population size and because its response to climate change and human interventions is unknown. In this work, we showed the encounter rates of humpback whales in their breeding grounds in Costa Rica for breeding seasons comprised in the period 2000-2020. We analyze the influence of climatic indices that influence the Pacific and environmental variables related to temperature and productivity in the feeding grounds of this population (United States). We hypothesize that the more intense the warming events, the fewer humpback whales complete their migration to Costa Rica. We conclude that the humpback whales of this population could be finding thermally favorable areas in intermediate latitudes (p. e.g., Mexican-Guatemala coasts), which could be related to the decreases in the presence of humpback whale adults and calves in Costa Rica. These observed changes could inform how humpback whales might respond to climate change.